Innovations in Islamic Religious Education in Bilingual Madrasah Aliyah: A Systematic Literature Review - Machfud Bachtiyar; M Yunus Abu Bakar; Evi Fatimatur Rusydiyah (STAI Hubbulwathan Duri, 2025)
In response to evolving educational demands, especially in the post-COVID-19 context, Madrasah Aliyah Bilingual has implemented various learning innovations aimed at enhancing educational quality and student outcomes. This study employs a Systematic Literature Review (SLR) to examine and synthesize learning innovations adopted by the institution. Sources were selected based on relevance, credibility, and contribution to the understanding of innovation in Islamic education. The findings reveal three major innovation themes: (1) Digital technology integration, including the use of podcasts and virtual platforms to sustain learning continuity and boost student motivation; (2) Adaptive curriculum development, exemplified by strategic library management and the Bilingual Class System to foster reading interest and global readiness; and (3) Interactive pedagogical approaches, such as the